Family role in preserving Javanese culture, values, and language: The challenges in the globalization 4.0 era - Nita Maghfiratul Jannah; Kurnia Lestari; Gregorius Jhonathan; Murni Sekar Pinilih; Ari Nurhayati; Margana Margana (Jurnal Penelitian Humaniora, 2023)
Along with the rise of the impact of globalization 4.0 that blurs the boundaries between countries and competition at the world level, many indigenous cultures have been pushed aside. Many families consider other cultures to be more advanced and educate children in contemporary culture that does not reflect their cultural identity. Efforts to preserve the nation's original culture need to be carried out from the family level. This quantitative study was aimed at determining factors influencing children's language development and the role of the family and the challenges in the effort of preserving Javanese culture, values, and languages in the globalization 4.0 era. The population of the study was the family whose kid around 3-12 years old domicile in Central Java and Yogyakarta. In total 94 samples were chosen using a random purposive  method.    The data were gathered  using  questionnaires  then analyzed  using  a descriptive quantitative  method.  The result  of the study  shows  that  family  roles  impact children's acquisition of Javanese. Environment, language level or social strata in language, media, and parental inability are the most common reasons why Javanese is considered difficult. This article also suggests solutions and gives other related data to support this study